Improvement to long-wavelength Australian gravity anomalies expected from the CHAMP, GRACE and GOCE dedicated satellite gravimetry missions - Featherstone, Will (CSIRO Publishing, 2003)
The concepts and mission parameters of the CHAMP, GRACE and GOCE dedicated satellite gravity missions are summarised, followed by the improvements that they are likely to make upon previous methods of determining the Earth's long-wavelength gravity field. An example of an error in the EGM96 global geopotential model, caused by the use of an incorrect digital elevation model over Australia, is used to exemplify the deficiencies in current global gravity models. Summarised results of a preliminary study to quantify long-wavelength errors in Australian gravity anomalies using data from the GRACE-derived EIGEN-2 global geopotential model indicate the presence of longwavelength (>1113 km) errors of over 10 mGal in Australian terrestrial gravity anomalies. Finally, the likely prospects for improved geophysical studies are speculated upon.